2009
DOI: 10.1017/s0022029908003841
|View full text |Cite
|
Sign up to set email alerts
|

Forage to concentrate ratio in Jonica breed goats: influence on lactation curve and milk composition

Abstract: The aim of the work is to evaluate the effects of different forage to concentrate rations on milk yield, composition and renneting properties of milk of Jonica breed goats. Twenty-four Jonica goats received diets with forage to concentrate ratio of 35/65, 50/50 or 65/35, providing respectively a low, medium and high energy level. Goats were divided into three homogenous groups and confined in individual pens for 152 days to assess the daily feed intake and milk yield and composition. The main conclusions show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
5
11
0
Order By: Relevance
“…Nevertheless, in this research, the rate of yield increased from 0.18 to 0.24, which agrees with Zambom et al (2005), who found values ranging from 0.10 to 0.27, and Tufarelli et al (2009), whose values ranged from 0.21 to 0.29 for the increased rate of yield until lactation peak. The largest values in this research may be related to animal genetics, intake of dry matter, or diet compositions.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, in this research, the rate of yield increased from 0.18 to 0.24, which agrees with Zambom et al (2005), who found values ranging from 0.10 to 0.27, and Tufarelli et al (2009), whose values ranged from 0.21 to 0.29 for the increased rate of yield until lactation peak. The largest values in this research may be related to animal genetics, intake of dry matter, or diet compositions.…”
Section: Discussionsupporting
confidence: 79%
“…But forage to concentrate ratio in this trial might not affect milk yield and milk composition since their rations were not significantly different as shown in Table 2. As reported by Tufarelli et al (2009), ratio 35/65 forage to concentrate provided greater milk yield compared to 50/50 ratio and 65/35 ratios without influencing milk composition during lactation period of Jonica breed goats.…”
Section: Milk Constituents and Composition Yieldsmentioning
confidence: 51%
“…The different levels of protein and energy response on milk yields and milk composition yields between different research reports might be due to many factors such as forage to concentrate ratio (Tufarelli et al 2009;Park et al 2010), breed and traits (Ciappesoni et al 2004). But forage to concentrate ratio in this trial might not affect milk yield and milk composition since their rations were not significantly different as shown in Table 2.…”
Section: Milk Constituents and Composition Yieldsmentioning
confidence: 86%
“…In this framework, it has been reported that in goat administered with forage to concentrate ratio as well as with discarded dates there was a remarkable increase in milk production [19,20].…”
Section: Discussionmentioning
confidence: 97%